1979
DOI: 10.1136/jcp.32.4.325
|View full text |Cite
|
Sign up to set email alerts
|

Studies of plasma zinc, copper, caeruloplasmin, and growth hormone

Abstract: SUMMARY The levels of plasma zinc, copper, caeruloplasmin, and growth hormone were determined in a group of normal people and in four groups of patients who were suffering from carcinoma of the bronchus, other forms of malignancy, chest illnesses, and diseases other than chest illness or malignancy. The plasma zinc was higher, and the plasma copper lower, in people without malignancy below the age of 30 years than they were in other age groups.It was confirmed that about 66 % of patients with carcinoma of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
1

Year Published

1980
1980
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 25 publications
1
23
0
1
Order By: Relevance
“…However, Linder et al [16] have noted that in normal serum 67% of SCu is bound to ceruloplasmin, whereas in a cancer patient the proportion of the Cu contained in cer uloplasmin is reduced. Nevertheless SCP also increases in patients with malignant tumors [2,14], and in our study it was higher in patients with high SCu. The as says of SCP in healthy subjects, patients with nonmalignant lung disease, patients with lung cancer and patients with other malignancies performed by Linder et al [15] confirmed that SCP was higher in pa tients with malignant disease than in heal thy subjects, but such assays still had only limited value in distinguishing nonmalig nant lung disease from malignant cases.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…However, Linder et al [16] have noted that in normal serum 67% of SCu is bound to ceruloplasmin, whereas in a cancer patient the proportion of the Cu contained in cer uloplasmin is reduced. Nevertheless SCP also increases in patients with malignant tumors [2,14], and in our study it was higher in patients with high SCu. The as says of SCP in healthy subjects, patients with nonmalignant lung disease, patients with lung cancer and patients with other malignancies performed by Linder et al [15] confirmed that SCP was higher in pa tients with malignant disease than in heal thy subjects, but such assays still had only limited value in distinguishing nonmalig nant lung disease from malignant cases.…”
Section: Discussionmentioning
confidence: 60%
“…Andrews [2] has suggested that plasma Cu values higher than 26.5 ¿¿mol/1 support a diagnosis of lung cancer, since 65% of his patients with bronchial carci noma against only 6% of the healthy sub jects or those suffering from nonmalignant chest disease had a copper level over 26.5 /tmol/1. In our study, only 15% of the patients with malignant or nonmalignant lung disease had values that high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased Zn and increased Cu levels have been con sistently reported in the serum of lung cancer patients [9][10][11][12]. A high level of Cu, calcium and Mg have been dem onstrated in malignant lung tissue [1], However, contra dictory data exist on the usefulness of trace metal mea surements in the diagnosis and prognosis of cancer [13], We demonstrated significantly higher Cu and Mg levels in the serum of patients both with malignant and nonmalignant pleural diseases compared to healthy subjects.…”
Section: Discussionmentioning
confidence: 92%
“…in pregnancy (Lahey et al, 1953), infection Correspondence and requests for reprints: Dr Aberdeen, Foresterhill, Aberdeen. (Markovitz et al, 1955) and in other malignancies (Fisher & Shifrine, 1978;Andrews, 1979). The significance of raised copper levels in malignancy has been debated (Pocklington & Foster, 1977).…”
mentioning
confidence: 99%